A Friend virus mutant that overcomes Fv-2rr host resistance encodes a small glycoprotein that dimerizes, is processed to cell surfaces, and specifically activates erythropoietin receptors. - Kozak, S L (1993)
The env gene of Friend spleen focus-forming virus (SFFV) encodes a membrane glycoprotein (gp55) that is inefficiently (3 to 5%) processed from the rough endoplasmic reticulum to form a larger dimeric plasma membrane derivative (gp55p). Moreover, the SFFV env glycoprotein associates with erythropoietin receptors (EpoR) to cause proliferation of infected erythroblasts [J.-P. Li, A. D. D'Andrea, H. F. Lodish, and D. Baltimore, Nature (London) 343:762-764, 1990]. Interestingly, the mitogenic effect of SFFV is blocked in mice homozygous for the Fv-2r resistance gene, but mutant SFFVs can overcome this resistance. Recent evidence suggested that these mutants contain partial env deletions that truncate the membrane-proximal extracellular domain of the encoded glycoproteins (M. H. Majumdar, C.-L. Cho, M. T. Fox, K. L. Eckner, S. Kozak, D. Kabat, and R. W. Geib, J. Virol. 66:3652-3660, 1992). Mutant BB6, which encodes a gp42 glycoprotein that has a large deletion in this domain, causes erythroblastosis in DBA/2 (Fv-2s) as well as in congenic D2.R (Fv-2r) mice. Analogous to gp55, gp42 is processed inefficiently as a disulfide-bonded dimer to form cell surface gp42p. Retroviral vectors with SFFV and BB6 env genes have no effect on interleukin 3-dependent BaF3 hematopoietic cells, but they cause growth factor independency of BaF3/EpoR cells, a derivative that contains recombinant EpoR. After binding 125I-Epo to surface EpoR on these factor-independent cells and adding the covalent cross-linking reagent disuccinimidyl suberate, complexes that had immunological properties and sizes demonstrating that they consisted of 125I-Epo-gp55p and 125I-Epo-gp42p were isolated from cell lysates. Contrary to a previous report, SFFV or BB6 env glycoproteins did not promiscuously activate other members of the EpoR superfamily. Although the related env glycoproteins encoded by dualtropic murine leukemia viruses formed detectable complexes with EpoR, strong mitogenic signalling did not ensue. Our results indicate that the SFFV and BB6 env glycoproteins specifically activate EpoR; they help to define the glycoprotein properties important for its functions; and they strongly suggest that the Fv-2 leukemia control gene encodes an EpoR-associated regulatory factor.